2013
DOI: 10.1021/ic401681r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monomeric MnII/III/IV–Hydroxo Complexes from X- and Q-Band Dual Mode Electron Paramagnetic Resonance (EPR) Spectroscopy

Abstract: Manganese–hydroxo species have been implicated in C–H bond activation performed by metalloenzymes, but the electronic properties of many of these intermediates are not well characterized. The present work presents a detailed characterization of three Mnn–OH complexes (where n = II, III, and IV) of the tris[(N′-tert-butylureaylato)-N-ethylene]aminato ([H3buea]3−) ligand using X- and Q-band dual mode electron paramagnetic resonance (EPR). Quantitative simulations for the [MnIIH3buea(OH)]2− complex demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 43 publications
20
53
0
Order By: Relevance
“…Our analysis of the EPR data showed that two distinct Mn IV –OH species are formed, a result that is similar to what we reported for [Mn IV H 3 buea(OH)]. 30,45 The largest difference between the two species for [Mn IV H 2 pout(OH)] is in their E/D values: species 1 ( E/D = 0.33) is significantly more rhombic than species 2 ( E/D = 0.17). The effective g-tensors for the |±1/2> and excited |±3/2> doublets for the two species are reported in Table 3 and indicated on Figure 8.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our analysis of the EPR data showed that two distinct Mn IV –OH species are formed, a result that is similar to what we reported for [Mn IV H 3 buea(OH)]. 30,45 The largest difference between the two species for [Mn IV H 2 pout(OH)] is in their E/D values: species 1 ( E/D = 0.33) is significantly more rhombic than species 2 ( E/D = 0.17). The effective g-tensors for the |±1/2> and excited |±3/2> doublets for the two species are reported in Table 3 and indicated on Figure 8.…”
Section: Resultssupporting
confidence: 90%
“…The EPR spectrum of [Mn II H 2 pout(OH)] 2- (Figure 6) in perpendicular-mode showed signals over a wide magnetic field range. The spectra are complicated by resonances from multiple overlapping transitions as has been described previously for [Mn II H 3 buea(OH)] 2- 45. The simulation overlaid on the experimental spectrum in Figure 6 is for a S = 5/2 spin center using the parameters of described in Table 2.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(Table 2). Attempts to prepare the analogous Mn II -oxo complex were unsuccessful because the oxido ligand is too basic (22), but we have previously reported the isolation of [Mn II H 3 buea(OH)] 2− , which has an experimental value of jA FC j = 250 MHz (32). We examined the changes in A FC for this series of manganese complexes spanning four consecutive oxidation states with nearly identical molecular structures.…”
Section: Resultsmentioning
confidence: 99%
“…5c A detailed analysis of the EPR properties for the three Mn–OH complexes has been described in a separate report. 14 …”
Section: Results ‡mentioning
confidence: 99%